2018
DOI: 10.1111/cxo.12623
|View full text |Cite
|
Sign up to set email alerts
|

Validation of keratometric measurements obtained with an intraoperative image‐guided system: intra‐session repeatability and interchangeability with an optical biometer

Abstract: The Verion system provides consistent measurements of keratometric parameters, with measurements of AX1 that are not interchangeable with that provided by the optical biometer Aladdin, especially in cases of low and oblique astigmatism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…23,24 Furthermore, the toric IOL calculation with the Verion system should be done carefully because different studies have demonstrated that its keratometry is not completely interchangeable with other commercial devices. [31][32][33][34] Nonetheless, in the current study, it should be noted that keratometry for calculating the toric IOL was measured with the IOLMaster 700 biometer, instead of with the Verion system.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Furthermore, the toric IOL calculation with the Verion system should be done carefully because different studies have demonstrated that its keratometry is not completely interchangeable with other commercial devices. [31][32][33][34] Nonetheless, in the current study, it should be noted that keratometry for calculating the toric IOL was measured with the IOLMaster 700 biometer, instead of with the Verion system.…”
Section: Discussionmentioning
confidence: 99%
“… 9 Ruiz-Belda et al evaluated 53 healthy eyes and recorded a mean S w of 0.26 and 0.24 D for K1 and K2, respectively; recently, Fukumitsu et al, for 69 cataract eyes, reported S w values of 0.03 to 0.05 mm and 0.03 to 0.09 for AL and ACD, respectively. 10 , 11 …”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding, eyes with cataract showed a high repeatability only for the AL, ACD, and K measurements, whereas WTW had a CoR value of 0.80 mm and an ICC of 0.795. Sabatino 10,11 AL-Scan Huang et al analyzed intraoperator repeatability for 68 cataract eyes measured by 2 operators. 12 They found CoV values for the first operator of 0.35%, 0.64%, 0.27%, 0.34%, 0.08%, 1.70%, and 5.46% for CCT, ACD, K1, K2, AL, WTW, and PD, respectively, and concluded that it provides highly repeatable measurements of CCT, ACD, AL, and K. Srivannaboon et al measured 137 eyes showing good repeatability for K, AL, ACD, and WTW (ICC >0.94); Kola et al supported their conclusions, obtaining ICC values of >0.937 for K1, K2, WTW, CCT, ACD, and AL and 0.87 to 0.90 for PS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…V arious instruments working with distinct optical principles to supply a detailed analysis of anterior segment structure and corneal shape have improved in recent times. 1,2 Multiple studies have compared the measurements between these different devices in healthy subjects; [1][2][3][4][5][6][7][8][9] however, there are a limited number of studies of keratoconus patients. 10,11 Analysis of the anterior segment parameters is necessary to diagnose keratoconus and to help make decisions about treatment, grading, and follow-up.…”
mentioning
confidence: 99%